Prefrontal Lobe Growth Disturbance in a Patient with Frontal Absence Seizures - Kanemura, Hideaki; Ohyama, Tetsuo; Mizorogi, Sonoko; Sugita, Kanji; Aihara, Masao (Journal of Pediatric Epilepsy, 2016)
Absence seizures sometimes present in patients with frontal lobe epilepsy. Cognitive and behavioral problems in patients with absence seizures may be correlated with frontal lobe dysfunction. We report a 15-year-old female patient with absence seizures. She showed learning and behavioral problems such as inattention and impulsivity. We studied serial changes in frontal and prefrontal lobe volume to clarify such correlations among three-dimensional magnetic resonance imaging (MRI). We compared frontal and prefrontal lobe volumes between this patient, the childhood absence epilepsy group (n = 4, age 8–11 y), and controls (n = 10, age 6–15 y). Three-dimensional MRI was performed four times in the case (at worsening of absence seizures and 1, 2, and 4 y later) and three times in the childhood absence epilepsy group (at onset and 1 and 2 y later). Even after the complete cessation of seizures, frontal and prefrontal lobe volumes were lower in the case than in patients with childhood absence epilepsy and control subjects. Also, prefrontal-to-frontal lobe volume ratio increased over time in the childhood absence epilepsy and control subjects, whereas its increase was slight in the case. Patients presenting with frontal absence may show prefrontal lobe growth disturbance, which may manifest as poor frontal lobe function.
Keywords: absence seizure; frontal lobe epilepsy; prefrontal lobe; brain volumetry; behavior